Exploring Lifestyle Activities to Reduce Internalized Ageism: Self-Efficacy as a Mediator Between Exercise, Volunteering, Computer Use, and Self-Perceptions of Aging. (April 2022) - Steward, Andrew; Hasche, Leslie
The objective of this study is to test self-efficacy as a mediator in the relationship between three lifestyle activities (exercise, volunteering, and computer use) and self-perceptions of aging (SPA) among older adults. We hypothesize that increased self-efficacy will mediate the relationship between lifestyle activities and more positive SPA. This is a cross-sectional, secondary data analysis drawn from the 2016 wave of the Health and Retirement Study (HRS; n = 4, 561). Bootstrapping procedures were applied to test the significance of the indirect effects of self-efficacy in the relationship between lifestyle activities and SPA. Results indicate significant direct effects between exercise, computer use, and self-efficacy. Direct effects were observed between exercise, volunteering, computer use, and SPA. Self-efficacy partially mediated the relationship between exercise, volunteering, computer use, and SPA. Implications for practitioners working with older adults are discussed. Future research should test formal intervention programs aimed at reducing internalized ageism through additional pathways.